INFLUENCE OF CAPITAL STRUCTURE, COMPANY GROWTH, COMPANY SIZE AND PROFITABILITY ON COMPANY VALUE IN INSURANCE COMPANIES - Melysa Marga Retha Sihombing; Jessy Safitri sitorus; Titin romauli Sibarani; Suryanty Pasaribu (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This observation was conducted in order to determine the effect of capital structure, firm growth, firm size and profitability on firm value. The results of the t-test in this study show that only profitability has a significant effect on firm value. The results of the f test on this observation indicate that the capital structure, firm growth, firm size and profitability do not simultaneously affect firm value